Review on the Security Issues in Human Sensor Networks for Healthcare Applications - Rani Chintala, Radhika; Rao M R, Narasinga; Venkateswarlu, Somu (International Journal of Engineering and Technology, 2018)
Human Sensor Network (HSN) is an emerging technology that allows to remotely monitor, gather and maintain the information of patientâ€™s health parameters using bio-sensors. The bio-sensors are either implantable or wearable or may be stitched on the clothes of a patient.The collected health information is processed and maintained in a database server. The information from the database can be accessed by the users such as doctors, health servants, government, insurance agencies and by the patient or his relatives. Since, the information collected is related to thepatientâ€™s private health record, it is required to be safely stored and protected from an unauthorized access. Thus, Security and Privacy are the key issues in HSNs.In this paper, the infrastructure-based and adhoc-based communication architecture of HSN and challenges and measures of security and privacy issues have been reviewed.Â Â